Quality of guava fruits bagged with different materials in an organic system - Neto, Sebastião Elviro de Araújo; Rocha, Cleb; de Farias, Josianny Feitosa; Minosso, Shirlei Cristina Cerqueira; Ferreira, Regina Lúcia Félix (Comunicata Scientiae, 2020)
This study aimed to evaluate the interference of bagging materials on the incidence of insect larvae and the physical and chemical quality of the guava cv. Paluma in an organic system. The experimental design was in randomized blocks with seven treatments and four replications of 25 fruits each. The bagging materials (treatments) were: nonwoven fabric (TNT), transparent plastic bag, white plastic bag, parchment paper, kraft paper, and non-bagged fruits (control). The titratable acidity (TA), ascorbic acid, soluble solids (SS), SS/TA ratio, fresh mass, fruit diameter, fruit length, appearance, and fruit fly incidence were evaluated. Fruit bagging increased the fresh fruit mass, except the tulle bag, which did not change fruit diameter but increased fruit length. There was a high incidence of fruit flies in the non-bagged fruits (100%) and in those with tulle bags (56.53%), reduced to 2.15% when using parchment paper, and reaching the absence of bored fruits when using nonwoven fabric, transparent plastic, and white plastic bags, materials that provided the highest percentages of marketable fruits. All bagging materials did not change the total titratable acidity content and the SS/TA ratio; however, all of them reduced the content of total soluble solids, except the tulle bag. Fruit bagging with nonwoven fabric and parchment paper increased the content of ascorbic acid. Fruit bagging with parchment paper, plastic bag, and nonwoven fabric are efficient in the organic production of guavas for preventing the infection by insect larvae and maintaining the physical and chemical quality of the fruit.